Industry 4.0 Incentives for Environmental Management Accounting - Medved, Ivana; Jovanović, Dejan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
In the past three decades, there has been an increasing need to incorporate the benefits of proactive environmental efforts into sustainable corporate business. Corporate sustainability as a concept is very complex, which is why in many entities environmental accounting and environmental management accounting are not yet sufficiently respected or accepted. The reasons are mainly due to incomplete data or inability to adequately collect data related to the environmental impact of the entity's business. The paper gives a brief overview of the capabilities of Industry 4.0 known as the fourth industrial revolution or the Internet of things. The circumstances and incentives of Industry 4.0 on environmental accounting and in particular on environmental management accounting were discussed. Management accounting techniques and practices for environmental purposes are focused on making timely and relevant eco-business decisions. For the purpose of gathering data for such business decision-making, it is necessary to adapt the entity's management control systems and establish an infrastructure for collecting and sharing information in supply chains. The goal of environmental management accounting is to collect data and make business decisions that will improve economic and environmental performance expressed through eco-efficiency. The purpose of the paper is to identify the benefits of Industry 4.0 for environmental management accounting and sustainable corporate business as well as the potential for better acceptance of environmental accounting and environmental management accounting.